Comparative Study of Catalytic Systems Formed by Palladium and Acyl‐Substituted Imidazolium Salts. Issue 3 (18th January 2018) - Gisbert, Patricia; Trillo, Paz; Pastor, Isidro M.
Abstract: Amino amides, which are readily accessible from amino acids, were used in the preparation of both monoamido and diamido functionalized imidazolium salts in very straightforward protocols. Different catalytic systems formed with palladium(II) acetate and acyl functionalized imidazolium salts were tested in the Matsuda‐Heck reaction. The comparative study revealed that the presence of one carbamoyl moiety in the N‐heterocyclic carbene precursor is more beneficial during the catalytic process. Thus, better activity was observed with the catalytic system formed using 3‐benzyl‐1‐( N ‐phenylcarbamoylmethyl)imidazolium chloride in a 1:1 metal/ligand ratio. Moreover, this fact was evidenced by means of UV/vis studies. Abstract : The comparison of different acyl functionalized imidazolium salts as precursors proved that carbamoyl moiety is more beneficial than others related acid derivative moieties. The catalytic activity of palladium is enhanced during the coupling reaction by the presence of an equimolecular amount of the imidazolium salt. The carbamoyl functionalized imidazolium salts are readily accessible from amino acids, formaldehyde and glyoxal, via straightforward protocols.